Barriers to obstetric fistula treatment in low‐income countries: a systematic review. Issue 8 (20th July 2017) - Baker, Zoë; Bellows, Ben; Bach, Rachel; Warren, Charlotte
Abstract: Objective: To identify the barriers faced by women living with obstetric fistula in low‐income countries that prevent them from seeking care, reaching medical centres and receiving appropriate care. Methods: Bibliographic databases, grey literature, journals, and network and organisation websites were searched in English and French from June to July 2014 and again from August to November 2016 using key search terms and specific inclusion and exclusion criteria for discussion of barriers to fistula treatment. Experts provided recommendations for additional sources. Results: Of 5829 articles screened, 139 were included in the review. Nine groups of barriers to treatment were identified: psychosocial, cultural, awareness, social, financial, transportation, facility shortages, quality of care and political leadership. Interventions to address barriers primarily focused on awareness, facility shortages, transportation, financial and social barriers. At present, outcome data, though promising, are sparse and the success of interventions in providing long‐term alleviation of barriers is unclear. Conclusion: Results from the review indicate that there are many barriers to fistula treatment, which operate at the individual, community and national levels. The successful treatment of obstetric fistula may thus require targeting several barriers, including depression, stigma and shame, lack of community‐based referral mechanisms, financial cost of the procedure, transportation difficulties, gender power imbalances, the availability of facilities that offer fistula repair, community reintegration and the competing priorities of political leadership.